2015
DOI: 10.1111/1462-2920.13016
|View full text |Cite
|
Sign up to set email alerts
|

Deep transcriptome profiling of clinical Klebsiella pneumoniae isolates reveals strain and sequence type‐specific adaptation

Abstract: CitationDeep transcriptome profiling of clinical Klebsiella pneumoniae isolates reveals strain and sequence typespecific adaptation. 2015, 17 (11) isolates. While the core-transcriptome profiles varied substantially between groups of different sequence types, they were more homogenous among isolates of the same sequence type. We furthermore linked the detailed information on differentially expressed genes with the clinically relevant phenotypes of biofilm formation and bacterial virulence.This allowed for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 108 publications
(145 reference statements)
2
24
0
Order By: Relevance
“…Taken together, these findings suggest that CC258 and non-CC258 K. pneumoniae isolates differ from one another with respect to fundamental aspects of metabolism, including the metabolism of amino acids (2-phenylacetate) and fatty acids (9(Z)-octadecenoate, hexadecanoate, and pentadecanoate). Such fundamental metabolic differences are in agreement with the conclusions that have been drawn from prior studies, for example [10][11][12].…”
Section: Discrimination Between Cc258 and Non-cc258 Via Fame Profilessupporting
confidence: 91%
See 1 more Smart Citation
“…Taken together, these findings suggest that CC258 and non-CC258 K. pneumoniae isolates differ from one another with respect to fundamental aspects of metabolism, including the metabolism of amino acids (2-phenylacetate) and fatty acids (9(Z)-octadecenoate, hexadecanoate, and pentadecanoate). Such fundamental metabolic differences are in agreement with the conclusions that have been drawn from prior studies, for example [10][11][12].…”
Section: Discrimination Between Cc258 and Non-cc258 Via Fame Profilessupporting
confidence: 91%
“…A small number of studies have suggested that CRKP and carbapenem-susceptible K. pneumoniae (CSKP) differ from one another not only with respect to their underlying genetics, but also their transcriptomic and metabolomic fingerprints. For example, Bruchmann and colleagues demonstrated that K. pneumoniae isolates belonging to CC258 produced a distinct transcriptomic fingerprint relative to CSKP isolates belonging to a range of other sequence types (STs) [10]. Rees and colleagues demonstrated that CRKP isolates belonging to CC258 produced a distinct volatile metabolic signature relative to both CSKP isolates belonging to other STs, as well as CRKP isolates belonging to non-CC258 lineages [11].…”
Section: Introductionmentioning
confidence: 99%
“…The number of expressed genes ranged from 5613 to 5662, fairly stable among conditions. The presence of a large number of genes in the K. pneumoniae transcriptome is not unsual, as previous reports with multiple isolates found between 4744 and 5378 genes expressed, which is also dependent on the growth conditions [29]. The number of differentially expressed (DE) genes (relative to condition PB in Table 1; FDR≤0.01) were 838; 691; 2022; 2162 and 3488 DE genes in Kp13 strain (original strain), Kp13 Mg (PB+no magnesium), Kp13 Ca (PB+high calcium), Kp13 Fe (PB+high iron) and Kp13 pH (PB+low pH), respectively (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Both of these metabolites are implicated in a broad range of biological processes, with succinate acting as a key player in the citric acid cycle and the metabolism of various amino acids, and formate implicated in the metabolism of pyruvate and folate, as well as the response to oxidative stress 34,35 . Furthermore, Gene Ontology (GO) analysis of transcriptomic data collected by Bruchmann and colleagues 17 identified 232 biological processes that were significantly enriched in CP isolates belonging to clonal complex 258 (CC258) relative to a diverse collection of non-CP isolates. Some of the most significantly enriched GO terms included “response to stress” ( p  = 7.6 × 10 −7 ), “organonitrogen compound catabolic process” ( p  = 4.5 × 10 −8 ), and “cellular carbohydrate metabolic process” ( p  = 2.7 × 10 −4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, transcriptomic profiling of K . pneumoniae has revealed distinct profiles associated with carbapenemase-producing ST258 isolates compared with carbapenem-susceptible isolates belonging to other lineages, even with respect to genes that have no apparent relationship to carbapenem resistance 17 . Indeed, Bruchmann and colleagues demonstrated that nearly 1,200 unique transcripts were differentially abundant between ST258 and non-ST258 isolates of K .…”
Section: Introductionmentioning
confidence: 99%